Kajian Psikolinguistik: Terhadap Perkembangan Pemerolehan Bahasa Anak Usia Empat Tahun - Manullang, Syahma Fitri; Manullang, Elkana Pujiando; Singarimbun, Mia Anggreini Br (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine and describe the language acquisition system of children aged 4 years, especially which includes spoken words. The method used in this research is a descriptive qualitative method. The research subject was Revanya Ginting, a 4-year-old child. It can be concluded that: 1). The results of the Mean Length Utterance (MLU) calculation for 4-year-old Revanya were 2.68 words per utterance, and it can be concluded that the child's language acquisition is still not in accordance with Brown's MLU theory. In Brown's theory regarding MLU (mean length of utterance), at stage VI the age range of 4 years should be 4.5 utterances while Revanya is 2.68 utterances. 2) Research subjects are able to say basic sentence patterns such as: S+P+O, S+P.